THE TSIMSHIAN RAVEN RATTLE: AN ICONOGRAPHICAL ANALYSIS - Stevens, Frank (2011)
The hypothesis examined in this thesis is that the raven rattle is a meaningful reflection of some of the underlying principles of Tsimshian cosmology. Based partly on Panofsky's (1962, 1955) procedures of inconographical analysis, and partly on Boas's (1927) characteristic trait distinction the method applied entails an analysis of the composition of the rattle. It explores the relationship between the component parts of the rattle from different structural levels and from different positions. Following Panofsky the meanings of the parts and their combinations are derived by relating them to mythology, ceremonialism, social structure and chiefly roles. The next step is to "discover" the underlying principles which, according to Panofsky, reveal the "basic attitude of a nation" but which in a more general sense can be regarded as the cosmology of a culture. The iconographical analysis of the raven rattle revealed fine main cultural principles: namely transformation, anti-structure, contradiction, control and initiation. Since these five principles constitute also a part of the cosmology of the Tsimshian one infers that the iconography and the functional contexts of the rattle do reflect and are congruent with the cosmology. This is an argument which supports the hypothesis. I argue that whether the rattle is examined in terms of its iconographical organization or its social and ceremonial function, it can be shown to reflect some of the same principles which underlie the cosmology of the Tsimshian. Master of Arts (MA)